Pattern of Leptin Secretion and Oxidative Markers in Heat-Stressed Pigeons - Al-Azraqi, A.A. (International Journal of Poultry Science, 2008)
The effect of heat stress on oxidative stress was studied in pigeons. Pigeons were either kept at thermo neutral room at 22oC, 24 hours/day or heat stress room at 34oC for 8 hours/day followed by 22oC for the rest of the day during the 40 days experiment. Increased heterophils: lymphocyte ratio was evident indicating stress in pigeons. Parallel increase in leptin, metabolites and oxidative markers was observed suggesting a modulating role of leptin during oxidative stress in pigeons.